Preparation, Application and Enhancement Dyeing Properties of ZnO Nanoparticles in Silk Fabrics Dyed with Natural Dyes - Haijuan Du; Mengyuan Yue; Xin Huang; Gaigai Duan; Zhihui Yang; Weihan Huang; Wenjie Shen; Xiangfeng Yin (Nanomaterials, 2022)
In this study, ZnO nanoparticles were prepared by a hydrothermal method with varying the reaction times, material ratios and reaction temperatures. The samples were characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray Diffraction (XRD) and Fourier infrared spectroscopy (FTIR). It was shown that the material ratio significantly affected the structure and morphology of the synthesized ZnO nanoparticles, and then the uneven nano-octahedral structure, uniform nano-octahedral structure, nano-tubular structure, and nano-sheet structure could be obtained successively. The synthesized ZnO nanoparticles as mordant were used for the dyeing of silk fabrics with different natural dyes (tea polyphenols and hematoxylin). Moreover, they could improve the dyeing properties and fastness (wash and light) on silk fabrics to a certain extent.